2018
DOI: 10.1136/vr.104603
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of cognitive impairments in canine idiopathic epilepsy

Abstract: In humans, epilepsy can induce or accelerate cognitive impairment (CI). There is emerging evidence of CI in dogs with idiopathic epilepsy (IE) from recent epidemiological studies. The aim of our study was to assess CI in dogs with IE using two tests of cognitive dysfunction designed for use in a clinical setting. Dogs with IE (n=17) were compared against controls (n=18) in their performance in two tasks; a spatial working memory task and a problem-solving task. In addition, owners completed the Canine Cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Over one fifth (6/27; 22.2%) of dogs with IE that completed the training phase did not meet learning criterion compared to just 1/23 (4.3%) of controls. This may reflect the cognitive impairments recently identified in dogs with IE [14][15][16] , particularly in spatial working memory 16 . In contrast, in a recent study of 125 dogs trained on the same spatial discrimination, only one dog (0.8%) did not reach the same learning criterion after completing the training phase 56 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Over one fifth (6/27; 22.2%) of dogs with IE that completed the training phase did not meet learning criterion compared to just 1/23 (4.3%) of controls. This may reflect the cognitive impairments recently identified in dogs with IE [14][15][16] , particularly in spatial working memory 16 . In contrast, in a recent study of 125 dogs trained on the same spatial discrimination, only one dog (0.8%) did not reach the same learning criterion after completing the training phase 56 .…”
Section: Discussionmentioning
confidence: 85%
“…In addition to seizure activity, therapeutic attempts to reduce their frequency and/or severity may further impair QOL due to common aversive side-effects of anti-seizure drugs (ASDs); indeed, the side effects ataxia and lethargy are associated with a reduced owner-reported QOL 13 . IE is also associated with negative perturbations in behaviour and cognition, including decreased trainability 14 , signs of cognitive impairment 15,16 , increased attention seeking 17 , aggression 18 and ADHD-like behaviours e.g. behaviours associated with high excitement and/or poor impulse control 19,20 .…”
mentioning
confidence: 99%
“…Around one‐third of dogs continue to seizure despite appropriately managed polypharmacotherapy 8‐10 . In addition, behavioral and cognitive comorbidities occur in dogs with epilepsy, 11 such as anxiety 12,13 deficits in spatial memory, 14 or cognitive function 15,16 . Seizures, drug‐related adverse effects along with changes to behavior and cognitive capabilities all contribute to the reduction in quality of life (QoL) for both dogs and their owners 17‐21 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Shihab and colleagues showed that dogs with epilepsy have a higher risk of displaying fear/anxiety-type behaviors and defensive aggression and show abnormal perception (that includes barking without apparent cause, chasing shadows or lights, aimless pacing, and staring into space). Other studies also have established a relationship between idiopathic epilepsy and cognitive impairment in dogs [71,72]. Interestingly, this relationship seems to be bi-directional.…”
Section: Abnormalities In Laboratory or Imaging Work-up Examplesmentioning
confidence: 80%